2011
DOI: 10.1002/ep.10601
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical treatment of colour index reactive orange 84 and textile wastewater by using stainless steel and iron electrodes

Abstract: In this study, two case studies were carried out: Electrocoagulation (EC) of a reactive textile dye solution and a textile wastewater. Stainless steel (SS) and iron (Fe) electrodes were used as sacrificial electrodes in parallel connection modes. Effects of pH, current density, and operating time on performance of EC were investigated. Optimum parameters obtained from dye experiments were applied to treatment of the textile wastewater. According to the experimental results, SS electrodes were found to be super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 46 publications
1
17
0
2
Order By: Relevance
“…The obtained value at 20 mA/cm² was around 5.84KWh/m 3 over 15 minutes of electrolysis. As reported by Yuksel et al 15 stainless steel has the lowest power consumption in comparison with Iron electrodes.…”
Section: Power Consumptionmentioning
confidence: 67%
See 2 more Smart Citations
“…The obtained value at 20 mA/cm² was around 5.84KWh/m 3 over 15 minutes of electrolysis. As reported by Yuksel et al 15 stainless steel has the lowest power consumption in comparison with Iron electrodes.…”
Section: Power Consumptionmentioning
confidence: 67%
“…From the figure, it is observed that MB elimination at stainless steel electrodes was found to be better as compared to Iron electrodes. The higher efficiency of SS may be because stainless steel promotes a higher potential of direct oxidation of the dye due to its high overpotential of oxygen evolution reaction compared to Iron 15 . Hence, further experiments have been performed by keeping SS as electrodes.…”
Section: Effect Of Electrodes' Materials On Dye Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Secondary Reactions. Sodium chloride is used as an electrolyte and chloride anions are generated during the EC treatment which oxidizes into Cl 2 (g) by the following reaction: 12 Thus, chlorine, depending on the pH, forms various chlorine species (Cl 2 , HOCl, and ClO − ) in the EC reactor. Hypochlorous acid and hypochlorite are the main chlorine species present in water in the pH range 6−9.…”
Section: Introductionmentioning
confidence: 99%
“…Yüksel ve arkadaşları [34], orange 84 boyarmaddesinin elektrokimyasal işlem ile giderilmesi için paslanmaz çelik ve demir elektrotlar kullanarak bir karşılaştırma çalışması yapmışlardır. Aynı deney koşullarında paslanmaz çelik elektrodun demir elektroda nazaran daha az aşındığı ve daha az çamur ürettiği gözlenmiştir.…”
Section: Gi̇ri̇ş (Introduction)unclassified